2005
DOI: 10.1128/aac.49.12.5157-5159.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Voriconazole Combined with Micafungin against Candida , Aspergillus , and Scedosporium spp. and Fusarium solani

Abstract: Effects of voriconazole combined with micafungin against 101 isolates of Candida spp. and 100 isolates of filamentous fungi have been evaluated by in vitro checkerboard analysis. The combination was indifferent for 97% of the Candida isolates and synergistic for 64% of the filamentous fungi (79% for Aspergillus fumigatus).The combination of two antifungal agents, voriconazole (VRC) and micafungin (MFG), was assessed for synergism against clinically relevant yeasts and molds. So far, only one little in vitro st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 17 publications
(13 reference statements)
2
49
0
1
Order By: Relevance
“…were demonstrated for all echinocandins, with greater inhibition achieved for A. flavus. These results are in agreement with those published previously for caspofungin (1) but appear to be somewhat different from those of two other previous studies, which demonstrated a diminished inhibitory effect of micafungin against A. flavus compared to that against A. fumigatus or A. terreus by the XTT assay (15,17). However, in both of those studies, the final concentration of menadione added to the wells was 25 M, i.e., a concentration fourfold higher than the one (6.25 M) used in the present study.…”
Section: Discussionsupporting
confidence: 36%
“…were demonstrated for all echinocandins, with greater inhibition achieved for A. flavus. These results are in agreement with those published previously for caspofungin (1) but appear to be somewhat different from those of two other previous studies, which demonstrated a diminished inhibitory effect of micafungin against A. flavus compared to that against A. fumigatus or A. terreus by the XTT assay (15,17). However, in both of those studies, the final concentration of menadione added to the wells was 25 M, i.e., a concentration fourfold higher than the one (6.25 M) used in the present study.…”
Section: Discussionsupporting
confidence: 36%
“…The combination of voriconazole and amphotericin B with micafungin was synergistic against S. prolificans and S. apiospermum isolates, although at lower frequencies (31% to 75% of the tested isolates). For those isolates for which the interactions were not classified as synergistic, a significant reduction of the MICs were observed and no antagonism was found (188,489). This synergistic interaction could be explained by the different mechanisms of action of these drugs, where the action of one agent reduces the resistance to the second agent.…”
Section: In Vitro Susceptibilities To Combinations Of Antifungal Agentsmentioning
confidence: 95%
“…For such cases, MCFG and voriconazole (VRCZ) combination therapy is expected to be effective. 17,18) However, VRCZ exhibits various interactive effects, and thus, combination with other drugs including antifungal agents should be carefully implemented. Since it is desirable to measure the blood concentration during administration of VRCZ, measurement of blood concentrations of both MCFG and VRCZ may be necessary for treatment of intractable deep mycosis with concomitant MCFG and VRCZ.…”
Section: Discussionmentioning
confidence: 99%